IMPLEMENTASI PROGRAM PENGEMBANGAN KAWASAN MINAPOLITAN PERIKANAN BUDIDAYA DI RAJAPURBAWA KABUPATEN BANJARNEGARA - Wicaksono, Thomas Agung Bayu; Hidayat, Zainal; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Fisheries is human activities that deals with the management of resources and the utilization of biodiversity waters. In Indonesia according to law of Republic Indonesia no. 9/1985 and law of Republic Indonesia no. 31/2004 activities including in fishery started from before production, of production processing up to marketing that have been undertaken in a business systems fishery. In this way fisheries can be considered is a business agribusiness. The government made study of potentials in the fisheries sector where the trend in modern times is industrialization. While the findings in the field is of the increase in a good enough in term of production a food fish and the number of fisheries agents under cultivation that increase significantly. Of the findings that governments create a program that enables the formation of an industrial area good fishery of the stage before production, of production processing the result of production to the stages of marketing. The program is called Minapolitan program which was set in PERMENKP NO. PER.12/men/2010 about Minapolitan. The purpose of this research is to find the implementation of Minapolitan program in Rajapurbawa area in Banjarnegara regency and to know the motivation factor and an impediment to implementation of Minapolitan program in Rajapurbawa area in Banjarnegara regency. The theory used among others the theory of public administration, public policy, and the implementation of policy. Type of research is the type used by descriptive approach qualitative research method. The subjects in this research are 4 people who is chairman of the field in each team Minapolitan on them, and 2 people from a member of one of the field in the team Minapolitan on them. While data collection techniques conducted by interviews and the study of literature. Data analysis done by the technique of the data, the reduction of data, and withdrawal of the presentation of conclusions and verification. The results of the study showed that the implementation of the program Minapolitan in Banjarnegara regency seen from 5 policy indicators the accuracy still reap negative value where there was 3 indicators that has not been right and only 2 indicators that have done exactly in the implementation. This was due to the fact that various factors that hampers the implementation of programs namely resources, factors communication between the organization as disposition, and the organizational structure.